A 169mW Fully-Integrated Ultrasound Imaging Processor Supporting Advanced Modes for Hand-Held Devices - Lo, Yi-Lin; Lo, Yu-Chen; Yang, Chia-Hsiang (2023 IEEE Symposium on VLSI Technology and Circuits (VLSI Technology and Circuits), 2023)
This work presents the first fully-integrated imaging processor that can support both standard and advanced modes. The TX delays are shared for different firing angles in plane-wave beam-forming, reducing the number of stored delay values by 99.8%. Exchanging the processing order for the proposed coarse delay finding scheme reduces the storage size by 78.1% for elastography imaging. The chip dissipates 169mW at 200MHz from a 0.91V supply. It delivers a 20.3x higher beamforming rate with 6.7-to-36.6x less power dissipation than the state-of-the-art design, in addition to the capability for supporting advanced modes.